VD_FINDINFO Pron / 2012 / 219 vom 27. September 2012 - VD Tribunal cantonal (2012)
DÉCISION D'IRRECEVABILITÉ, MOTIVATION DE LA DEMANDE, VICE DE FORME | 132 al. 1 CPC (CH), 319 let. a CPC (CH), 321 al. 1 CPC (CH)